Hubungan Kekuatan Otot Lengan dan Koordinasi Mata-Tangan dengan Kemampuan Servis Bawah Bola Voli Siswa - Riko Ertanto; Muhammad Supriyadi; Wawan Syafutra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
This study aimed to determine the relationship between arm muscle strength and eye-hand coordination with the ability to serve under volleyball male extracurricular students at Air Satan State Junior High School, Musi Rawas Regency. This research method is a quantitative method with correlational test. The population in this study were male volleyball extracurricular students at Air Satan State Junior High School, Musi Rawas Regency. The sample taken from the total sampling result is 21 students. Data collection techniques using tests and measurements. Data analysis techniques used are normality test, Pearson product moment correlation test and multiple correlation test. The results obtained, 1) there is a significant relationship between arm muscle strength and the ability to serve under volleyball male extracurricular students of Air Satan State Junior High School, Musi Rawas Regency, with rcount = 0.728> rtable = 0.433; 2) there is a significant relationship between eye-hand coordination and the ability to serve under volleyball male extracurricular students of Air Satan State Junior High School, Musi Rawas Regency, with rcount = 0.795 > rtable = 0.433; 3) there is a significant relationship between arm muscle strength and eye-hand coordination of male extracurricular students at Air Satan State Junior High School, Musi Rawas Regency, with rcount = 0.871 > rtable = 0.433; 4) there is a significant relationship between arm muscle strength and eye-hand coordination together with the ability to serve under volleyball male extracurricular students of Air Satan State Junior High School, Musi Rawas Regency, with Rcount = 0.798 > Rtable = 0.433, Coefficient of Determination (KD) =63.6%. Conclusion, overall both simple and multiple. Keywords: Arm Muscle Strength, Lower Service Ability, Eye-Hand Coordination